UPAYA PENINGKATAN KESIAPSIAGAAN GURU DAN SISWA DALAM MENGHADAPI BENCANA GEMPA BUMI DAN KEBAKARAN DI SDN 01 SOROPIA, DESA WAWORAHA, KECAMATAN SOROPIA, KABUPATEN KONAWE TAHUN 2024 - Saptaputra, Syawal Kamiluddin (Anoa : Jurnal Pengabdian Masyarakat Sosial, Politik, Budaya, Hukum, Ekonomi, 2024)
Preparedness is a series of activities to anticipate disasters where increasing preparedness is an important activity to reduce disaster risk in various situations. The results of observations that have been made during field observations at SDN 01 Soropia found several problems such as the unpreparedness of schools in dealing with disasters where the lack of availability of school facilities needed in the event of a disaster. Therefore, it is necessary to make efforts to increase community preparedness and vigilance, especially school-age children and also school teachers of SDN 01 Soropia by providing socialization / education related to earthquake and fire disasters. The purpose of this service is to increase the knowledge and preparedness of students and teachers of SDN 01 Soropia regarding earthquake and fire disasters. The method used in the service is the education method in the form of offline. The result of this service is that teachers and students can understand and apply preparedness for earthquake and fire disasters to help prevent and reduce the impact of disasters that can occur.